Medication reconciliation by pharmacists for pre-admission patients improves patient safety - Yunami Yamada; Ryo Kobayashi; Taishi Yamamoto; Hironori Fujii; Hirotoshi Iihara; Kato-Hayashi Hiroko; Shohei Nishida; Ryo Hoshino; Takashi Niwa; Keisuke Kumada; Masahito Shimizu; Akio Suzuki (BMC, 2024)
Abstract Background Medication errors related to the pre-admission medication history obtained on admission are a major cause of medication error during hospitalization. Medication reconciliation (MR) improves patient safety through the detection of inadvertent medication discrepancies at transitions of care. The aim of this study was to evaluate the effect of MR by pharmacists for patients prior to hospital admission on the incidence of medication errors in the early post-admission period. Patients and methods Patients admitted to the orthopedic ward for surgery between April 2012 and March 2020 were included. Pharmacist-led MR for pre-admission patients was started on April 1, 2017. The incidence of medication errors related to pre-admission medications that occurred during hospitalization were compared between the pre- and post-initiation of pharmacist-led MR (pre-initiation: April 1, 2012 to March 31, 2015, post-initiation: April 1, 2017 to March 31, 2020). Result In the post-initiation group, 94.2% (1245/1321) of patients who were taking medications on admission had a pharmacist-led MR before admission. The proportion of patients whose physicians ordered the prescription of their pre-admission medications at the time before hospitalization to continue from admission was significantly higher in the post-initiation group than in the pre-initiation group (47.4% vs. 1.0%, p < 0.001). The incidence of medication errors related to pre-admission medications during hospitalization was significantly lower in the post-initiation group than in the pre-initiation group (1.83% vs. 0.85%, p = 0.025). Pharmacist-led MR prior to admission was a significant protective factor against incidents related to pre-admission medication (odds ratio (OR), 0.3810; 95% confidence interval (CI); 0.156-0.9320, p = 0.035). Conclusion Pharmacist-led MR for patients prior to hospital admission led to a reduction in medication errors related to pre-admission medications during hospitalization. Patient safety during hospitalization can be improved by accurate medication histories provided early by pharmacists.